INFLUENCE OF RHIZOBIUM INOCULATION AND GENOTYPE ON SOYBEAN [GLYCINE MAX (L.) MERRILL] PERFORMANCE UNDER CONTRASTING SOIL CONDITIONS IN THE SUDAN SAVANNA OF NIGERIA - Rabiu, R.T.; Musa, A.S.; Shittu, E.A.; Jibrin, M.S.; Hamisu, H.S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study evaluated the interactive effects of Rhizobium inoculation and soybean genotypes on growth, nodulation, and yield across two locations of Gaya and Bayero University Kano (BUK), with contrasting soil fertility profiles during the 2021 rainy season. The treatments consisted of two soybean varieties (TGX1447-2E and TGX1885-10E) and two inoculation levels (inoculated and uninoculated), factorialy combined and laid out in a randomized complete block design with three replications. Pre-planting soil analysis revealed that Gaya had higher organic matter (45 g kg⁻¹) and nitrogen (11 g kg⁻¹), while BUK was nitrogen-deficient (1.4 g kg⁻¹) but phosphorus-rich (188 mg kg⁻¹). Rhizobium inoculation significantly (P < 0.05) enhanced nodulation, pod weight, 100-seed weight, and grain yield at both sites. At Gaya, inoculation increased grain yield from 4,000.6 to 13,638.6 kg ha⁻¹ and 100-seed weight from 11.09 g to 13.67 g. At BUK, yield rose from 5,796.7 to 7,770.3 kg ha⁻¹ with inoculation, despite lower organic matter. TGX1885-10E performed best at Gaya, producing 11,833.1 kg ha⁻¹, while TGX1447-2E yielded 7,727.3 kg ha⁻¹ at BUK, indicating superior adaptation to low-nitrogen conditions. Although no significant interaction was observed between variety and inoculation, both factors independently improved performance of the crop. These findings underscore the importance of site-specific agronomic strategies, where inoculation combined with appropriate varietal selection can significantly boost soybean productivity and soil fertility in low-input farming systems across the Sudan savanna.